DIGITALISASI PEMERINTAHAN DESA: HAMBATAN DAN DAMPAKNYA BAGI TATA KELOLA DESA - Najich Alfayn, Mukhammad Akhmad; Laila Kholid Alfirdaus; Budi Setiyono (Universitas Islam Malang, 2022)
Village digitalization has been studied extensively as a subject worthy of in-depth investigation. This study was the beginning of mapping the effects, challenges, and impacts of rural digitalization. In practice, there were still various obstacles. This study's objective was to investigate the various elements that affect the viability of digitalization in a rural environment. The authors of this study used a qualitative study approach using literature review techniques to collect data and information regarding the implementation of e-government in the village. Supporting data could be obtained from reference books, news articles from the internet, and research journal publications. The findings of this study showed that global modernization and digitalization could not be separated if village governments did not want to be left behind. It was impacted by elements that hindered digitalization, such as demographics, distrust, value, competence, and complexity. Strategic actions must be implemented to maximize the implementation of village digitalization. This study had consequences for Indonesian public institutions, both theoretically and practically. It is possible to carry out further studies in the form of a village government digitalization plan.